From North Sea to the South China Sea: the implementation of Industry Mutual Hold Harmless (IMHH) deed in Asean oil and gas industry - Wan Zahari, Wan Mohd Zulhafiz (2019)
This research aims at determining the feasibility of implementing the Industry of Mutual Hold Harmless Deed (“IMHH”) in the ASEAN oil and gas industry legal framework. Currently, the IMHH applies to the UK’s territory of the North Sea and the Irish Sea. It was created to support and effectively manage the inherent risks in offshore activities in the oil and gas industry whereby a company is considerably in a better position will protect its own people and equipment by providing an indemnification. In this regard, companies are more certain of the risks they must insure and could avoid multiple insurance policies on the same risk. However, it is important to note that some modification of the IMHH model should be made to accommodate peculiar circumstances. In doing so, ASEAN policies and practices should be taken into consideration in the discussion. In addition, the local law of the respective ASEAN member states is equally essential to be analysed. Hence, the methodology employed in this research will be a comparative analysis which will be carried out in a descriptive, analytic and prescriptive manner.